Transcrições para piano: histórico e uma proposta de execução para a mão esquerda de alguns prelúdios de Chopin - Marcal Fernando Castellao (2009)
This document presents a brief history about musical transcription since Renaissance up to the 20th century and launches a discussion upon methodological approaches pointing out musical examples of outstanding composers. One of the main issues intends to demonstrate both the importance and validity of musical transcriptions. It intends to contribute to enrich this type of performance through the elaboration of arrangements for the left hand of some of the Preludes opus 28 by Chopin. An investigation about the performance practice of left hand alone is also done in order to both enhance the process of the transcriptions itself as well as its applications to the transcriptions presented in this document: six of the 24 Preludes opus 28 by Chopin.